HUBUNGAN WORK LIFE BALANCE TERHADAP KEPUASAN KERJA PADA PEKERJA DI PT INDONESIA POWER UNIT PLTU BANTEN 3 LONTAR OMU TAHUN 2022 - Sara Herna Cova Sihombing (2023)
Job satisfaction is a picture of a person's positive feelings towards his work. Job satisfaction at PT Indonesia Power Unit PLTU Banten 3 Lontar OMU in 2021 decreased by 83.30% or decreased by 0.95% compared to 2020 of 84.10%. Job satisfaction that is not achieved can increase turnover and absenteeism. The purpose of this study was to determine the relationship between work-life balance and individual factors (age, gender, and years of service) on job satisfaction. This study uses a quantitative method with a cross-sectional study approach with non-probability sampling using purposive sampling and the minimum number of samples required is 102 workers at PT Indonesia Power Unit PLTU Banten 3 OMU. The data collection technique used was a questionnaire distributed to workers via Google Forms. Data analysis used univariate analysis and bivariate analysis with the chi-square method (95% CI). The results of the analysis showed that there was no relationship between work-life balance (p=0.086), age (p=0.204), gender (p=0.085), and years of service (p=0.758) on job satisfaction. The conclusion from the results of this study is that there is no relationship between work-life balance and individual factors (age, gender, and years of service) on job satisfaction. It is suggested to PT Indonesia Power Unit PLTU Banten 3 OMU maintain and increase family gathering activities, minimize demands for work deadlines, and maintain a good division of tasks.